Resin composition, prepreg, circuit board and printed circuit board
By using a resin composition with a first resin having a ring-like conjugated structure and a second resin containing an unsaturated double bond, combined with a curing agent, a filler and an initiator, the problem of insufficient processing and forming performance of the circuit substrate when reducing CTE and warping is solved, and excellent circuit substrate performance is achieved.
Patent Information
- Application Number
- CN202311244785.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
While reducing the thermal expansion coefficient (CTE) and warpage, existing circuit substrates have poor processing and forming performance, which are prone to insufficient interlayer bonding force, cracking of hole walls and cracking between layers.
A resin composition is used, including a linear resin, a curing agent, a filler and an initiator that has a cyclic conjugated structure, a second resin containing an unsaturated double bond and does not contain branched chains. By regulating the molecular structure of the resin composition and the 1-hour half-life temperature of the initiator, the compatibility and bondability of the resin system are improved.
The circuit substrate is low CTE and low warpage, while improving its machining performance and forming performance, avoiding insufficient interlayer bonding force and other machining problems.
Smart Images

Figure BDA0004472866030000031 
Figure BDA0004472866030000051 
Figure BDA0004472866030000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic industry, and in particular to a resin composition, a prepreg, a circuit substrate and a printed circuit board. Background Art
[0002] With the rapid development of electronic technology and communication equipment, circuit substrates are required to develop in the direction of miniaturization, thinness, high integration and high reliability. In addition, due to the increasing requirements for semiconductor packaging density, in order to reduce the warping problem caused by the packaging process, there has been a strong demand in recent years to reduce the coefficient of thermal expansion (CTE) of the circuit substrate.
[0003] In the prior art, in order to achieve the effect of low CTE and low warpage of the circuit substrate, a relatively rigid resin system and a high filler content are usually selected for preparation. However, this solution will make the circuit substrate too brittle, resulting in poor interlayer bonding, easy hole wall cracking during drilling, and interlayer cracking during reflow soldering, resulting in board failure and other processing problems. Although the addition of tough resin can solve the problem of the circuit substrate being too brittle, there will be problems with the compatibility of the resin system, such as gaps between the formed circuit substrates. Summary of the invention
[0004] Based on this, it is necessary to provide a resin composition, a prepreg, a circuit substrate and a printed circuit board to address the above problems. The circuit substrate made of the resin composition has low CTE and low warpage, and also has excellent processing performance and forming performance.
[0005] A resin composition comprises a first resin, a second resin, a curing agent, a filler and an initiator, wherein the first resin has a cyclic conjugated structure in its molecular chain, the second resin is selected from a linear resin containing unsaturated double bonds and no branches, the one-hour half-life temperature of the initiator is H1, the curing temperature of the resin composition is H2, and H2-20≤H1≤H2+20.
[0006] In one embodiment, the curing temperature of the resin composition is 130°C to 250°C.
[0007] In one embodiment, the initiator is selected from peroxide initiator and / or carbon-based initiator.
[0008] In one embodiment, the initiator is selected from the peroxide initiator and the carbon-based initiator, wherein the peroxide initiator is selected from the first initiator and / or the second initiator, and the 1-hour half-life temperature of the first initiator is H 11 , 50℃≤H 11<120°C, the one-hour half-life temperature of the second initiator is H 12 , 120℃≤H 12 ≤190°C, the one-hour half-life temperature of the carbon-based initiator is H 13 , H 13 ≥190℃.
[0009] In one embodiment, the first initiator is selected from at least one of benzoyl peroxide, lauroyl peroxide or t-butyl peroxyvalerate;
[0010] And / or, the second initiator is selected from at least one of di-tert-butyl peroxycyclohexane, di-tert-butyl peroxyethyl butyrate, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, diisopropylbenzene peroxide or tert-butyl isopropylbenzene peroxide, tert-amyl hydroperoxide, isopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-dichloroperoxyhexane, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide or 1,1,3,3-tetramethyl hydroperoxide;
[0011] And / or, the carbon-based initiator is at least one selected from 2,3-dimethyl-2,3-diphenylbutane or p-isopropylbenzene polymer.
[0012] In one embodiment, the number average molecular weight of the second resin is 300 to 5000;
[0013] And / or, the second resin further includes terminal olefin groups, and the content of the terminal olefin groups in the second resin is 10 wt % to 60 wt %.
[0014] In one embodiment, the first resin is selected from at least one of maleimide resin, epoxy resin, benzoxazine resin, polyphenylene ether resin or polyimide resin.
[0015] In one embodiment, the molecular structure of the maleimide resin is formula (I):
[0016]
[0017] Wherein, n=3-48, R1 is an alkyl group or an ether bond, and R2 is an alkyl group.
[0018] In one embodiment, in the resin composition, based on 100 parts by weight of the first resin, the amount of the second resin is 5 parts by weight to 50 parts by weight, the amount of the curing agent is 30 parts by weight to 70 parts by weight, the amount of the filler is 50 parts by weight to 200 parts by weight, and the amount of the initiator is 0.005 parts by weight to 0.1 parts by weight.
[0019] In one embodiment, the filler is selected from inorganic fillers, and the filler is modified by a silane coupling agent.
[0020] In one embodiment, the silane coupling agent is selected from a first silane coupling agent and a second silane coupling agent, wherein the first silane coupling agent contains an alkenyl radical and has a carbon chain length of ≤6, the carbon chain length of the second silane coupling agent is >6, and / or the mass ratio of the first silane coupling agent to the second silane coupling agent is 1:0.05 to 1:1.5.
[0021] A prepreg made from the resin composition as described above.
[0022] A circuit substrate made of the prepreg as described above.
[0023] A printed circuit board made of the circuit substrate as described above.
[0024] In the resin composition of the present invention, by regulating the molecular structure of the first resin and the second resin, the circuit substrate obtained by molding the resin composition has low CTE and low warpage, and can improve the toughness of the circuit substrate, so that it has excellent processing performance; at the same time, the present invention further improves the compatibility of the resin system by limiting the 1-hour half-life temperature of the initiator, avoids agglomeration between the various components of the resin system, and has excellent molding performance. Furthermore, the circuit substrate obtained by molding the resin composition of the present invention has low CTE and low warpage, and also has excellent processing performance and molding performance. DETAILED DESCRIPTION
[0025] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0027] The resin composition provided by the present invention comprises a first resin, a second resin, a curing agent, a filler and an initiator, wherein the first resin has a cyclic conjugated structure in its molecular chain, the second resin is selected from a linear resin containing an unsaturated double bond and no branching, the one-hour half-life temperature of the initiator is H1, the curing temperature of the resin composition is H2, and H2-20≤H1≤H2+20.
[0028] In the resin composition of the present invention, by regulating the molecular structures of the first resin and the second resin, the circuit substrate obtained by molding the resin composition has low CTE and low warpage, and can improve the toughness of the circuit substrate, so that it has excellent processing performance. At the same time, the present invention further improves the compatibility of the resin system by limiting the 1-hour half-life temperature of the initiator, avoids agglomeration between the components of the resin system, and improves the bonding between the resin systems, thereby improving the CTE and warpage of the circuit substrate while improving the molding performance of the circuit substrate.
[0029] Therefore, the circuit substrate obtained by molding the resin composition of the present invention has low CTE and low warpage, and also has excellent processing performance and molding performance.
[0030] Optionally, the cyclic conjugated structure in the molecular chain of the first resin may be phenyl, naphthyl, anthracene, etc. Preferably, the first resin is selected from at least one of maleimide resin (BMI), epoxy resin, benzoxazine resin, polyphenylene ether resin or polyimide resin.
[0031] In order to make the circuit substrate made of the resin composition have lower CTE and lower warpage, the first resin is preferably BMI.
[0032] Further preferably, the structure of BMI is as shown in formula (I):
[0033]
[0034] In the formula, R1 is an alkyl group or an ether bond, R2 is an alkyl group, and n is an integer of 3 to 48, preferably an integer of 3 to 18. Thus, the circuit substrate made of the resin composition can have low CTE and low warpage while improving its compatibility with other components in the resin composition, further improving the forming performance of the circuit substrate.
[0035] Optionally, the number average molecular weight of the second resin is preferably 300 to 5000, so that the circuit substrate made of the resin composition can have better toughness and thus better processing performance.
[0036] Optionally, the second resin may also be provided with a terminal olefin group, and the content of the terminal olefin group in the second resin is 10wt% to 60wt%. Thus, the second resin can be connected to the cross-linked skeleton through polymerization reaction, which can not only promote the compatibility of the resin system, avoid agglomeration between the components of the resin system, and improve the forming performance of the circuit substrate, but also make the circuit substrate have better toughness and stress buffering performance, improve the processing performance of the circuit substrate, and thus the circuit substrate has low CTE and warpage performance while having excellent processing performance and forming performance.
[0037] Optionally, the second resin may be a resin containing structures such as allyl and vinyl. More preferably, the second resin is selected from at least one of a polyisobutylene resin containing an allyl structure and a vinyl-terminated polyisobutylene resin.
[0038] The curing temperature of the resin composition is determined by the curing reaction of each component. Optionally, the curing temperature H2 of the resin composition of the present invention is preferably in the range of 130°C to 250°C, and the 1-hour half-life temperature H1 of the initiator is adjusted within this range. By setting the curing temperature and the 1-hour half-life temperature of the initiator in this way, the circuit substrate is ensured to have excellent molding performance while having lower CTE and warpage performance.
[0039] In order to further improve the compatibility of the resin composition and the forming performance of the manufactured circuit substrate, the initiator is selected from a peroxide initiator and / or a carbon-based initiator. Further preferably, the initiator is selected from a peroxide initiator and a carbon-based initiator for compound use, and the peroxide initiator and the carbon-based initiator are designed according to a gradient-increasing half-life temperature, so as to further coordinate the curing temperature of the resin composition, so that the resin composition can react completely during the curing process, improve the compatibility of the resin system, reduce agglomeration, further improve the forming performance of the circuit substrate, and improve warpage and CTE.
[0040] Optionally, the peroxide initiator is preferably the first initiator and / or the second initiator, and the one-hour half-life temperature of the first initiator is H 11 , 50℃≤H 11 <120°C, the one-hour half-life temperature of the second initiator is H 12 , 120℃≤H 12 ≤190°C, the one-hour half-life temperature of the carbon-based initiator is H 13 , H 13 ≥190℃, more preferably, 190℃≤H 13 ≤250℃.
[0041] Optionally, the first initiator is preferably benzoyl peroxide (H11 =90℃), lauroyl peroxide (H 11 =80℃) or tert-butyl peroxyvalerate (H 11 =100°C); the second initiator is preferably di-tert-butyl peroxycyclohexane (H 12 =115°C), ethyl di-tert-butyl peroxybutyrate (H 12 =130°C), 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane ((H 12 =152℃), dicumyl peroxide (H 12 =140℃), tert-butylcumene peroxide (H 12 =120℃) or cumene hydroperoxide (H 12 =190°C); the carbon-based initiator is preferably 2,3-dimethyl-2,3-diphenylbutane (H 13 =220℃) or p-cumene polymer (H 13 =230°C).
[0042] Specifically, when the initiator is a compound of a peroxide initiator and a carbon-based initiator, the 1-hour half-life temperature of the compound initiator can be controlled by adjusting the amount of the initiator, so that it is more conducive to the curing temperature of the resin composition. Preferably, the mass ratio of the peroxide initiator to the carbon-based initiator is preferably 3:1 to 6:1, and when the peroxide initiator includes a first initiator and a second initiator, the mass ratio of the first initiator to the second initiator is preferably 1:3 to 3:1.
[0043] Since the higher the filling rate of the filler in the resin composition, the easier it is to cause agglomeration, which will affect the compatibility of the resin composition, in order to further improve the compatibility of the resin composition, the filler is preferably modified with a silane coupling agent to improve the forming performance of the manufactured circuit substrate, thereby improving the CTE and warpage of the circuit substrate while also having excellent forming performance.
[0044] Preferably, the present invention uses a first silane coupling agent with a shorter carbon chain length and a second silane coupling agent with a longer carbon chain length for synergistic modification treatment.
[0045] Optionally, the carbon chain length of the first silane coupling agent is ≤6, and is preferably a silane coupling agent containing alkenyl radicals, so that the first silane coupling agent can undergo a cross-linking reaction with the components in the resin composition, thereby increasing the cross-linking density of the resin system, and thereby improving the compatibility and bonding strength of the filler with the resin system. Further preferably, the first silane coupling agent is selected from at least one of KBM974 or KBM573.
[0046] Optionally, the carbon chain length of the second silane coupling agent is greater than 6. Based on the longer molecular chain, the second silane coupling agent can improve the co-flowability of the filler and the resin system, thereby improving the compatibility of the filler and the resin system. Further preferably, the carbon chain length of the second silane coupling agent is less than 10, thereby improving the compatibility of the resin system while avoiding agglomeration caused by entanglement of the carbon chain with the resin system due to excessive length. Preferably, the second silane coupling agent is selected from at least one of KBM5803 or KBM6803.
[0047] Therefore, through the synergistic effect of the carbon chain length and different functions of the first silane coupling agent and the second silane coupling agent, the bonding force between the filler and the resin system can be ensured, the inorganic-organic compatibility can be enhanced, and the processing performance and forming performance of the circuit substrate can be improved.
[0048] In order to further increase the organic compatibility with the resin system, optionally, the mass ratio of the first silane coupling agent to the second silane coupling agent is 1:0.05 to 1:1.5, and more preferably 1:0.1 to 1:0.5, so that the two silane coupling agents with different carbon chain lengths and different functions can play a better synergistic role in the resin system.
[0049] Optionally, the specific type of the filler is not specifically limited. Preferably, the filler is an inorganic filler, and more preferably at least one of spherical silica, angular silica, fused silica, composite silicon powder, alumina, titanium dioxide or boron nitride.
[0050] In order to make the first resin, the second resin, the filler and the initiator play a better synergistic role, ensure that the resin composition has excellent toughness and compatibility, so that the circuit substrate made of the resin composition can further improve the processing performance and forming performance on the basis of meeting the low CTE and low warpage. In the resin composition, preferably, the amount of filler added is 0.5 to 2 times that of the first resin. Further preferably, based on 100 parts by weight of the first resin, the amount of the second resin is 5 to 50 parts by weight, the amount of the curing agent is 30 to 70 parts by weight, the amount of the filler is 50 to 200 parts by weight, and the amount of the initiator is 0.005 to 0.1 parts by weight.
[0051] Preferably, the initiator is selected from a peroxide initiator and a carbon-based initiator, and the amount of the peroxide initiator is 0.03 to 0.06 parts by weight. More preferably, the amount of the carbon-based initiator is 0.01 parts by weight.
[0052] Optionally, the curing agent is a polyalkenyl curing agent containing more than two alkenyl groups, so as to provide a better curing effect and further improve the compatibility of the resin system when combined with the second resin. It is preferably at least one of triallyl isocyanurate, diallyl aniline, divinylbenzene or trivinylbenzene.
[0053] Optionally, the molecular structure of the curing agent also includes a carbon-nitrogen heterocycle, which promotes the curing reaction, further increases the crosslinking density, and thereby improves the compatibility of the resin system while reducing CTE and warpage, thereby improving the forming performance of the circuit substrate. The curing agent is preferably at least one of 1,3-divinyl-2-imidazolidinone or 1,3,5-triacryloylhexahydro-1,3,5-triazine.
[0054] The present invention also provides a prepreg made of the resin composition as described above. The present invention does not limit the specific preparation method of the prepreg using the resin composition. Specifically, a solvent may be added to the resin composition. The amount of solvent added is selected by a person skilled in the art based on experience and process requirements to make the resin composition reach a viscosity suitable for use. The resin composition is then used to impregnate or coat a reinforcing material and dried to obtain a prepreg. During the drying process, the solvent in the resin composition will partially or completely evaporate. The present invention does not limit the type of solvent, which is a common commercially available organic solvent, such as butanone. The type of reinforcing material is not limited, and is preferably glass fiber cloth, such as 1078E cloth.
[0055] The present invention also provides a circuit substrate, comprising an insulating layer and a conductive layer arranged on at least one surface of the insulating layer, wherein the insulating layer is pressed from one or at least two superimposed semi-cured sheets as described above, and the circuit substrate has low CTE and low warpage as well as excellent toughness and compatibility, and thus has excellent processing performance and forming performance.
[0056] Specifically, the thermal expansion coefficient of the circuit substrate is evaluated based on the thermal expansion coefficient of the circuit substrate in the XY axis (perpendicular to the thickness direction), and a CTE of ≤10 is considered to meet the standard.
[0057] The warping performance of the circuit substrate is evaluated by the bending modulus of the circuit substrate, and a bending modulus ≥ 21 is considered to meet the standard.
[0058] A load is applied to the circuit substrate, and the longitudinal and transverse lengths of the crack are tested respectively. Based on the longitudinal and transverse lengths at 10 positions, an average value X of the crack length is calculated. The processing performance of the circuit substrate is evaluated by impact cracks, and an average value X ≤ 1000 μm is considered to meet the standard.
[0059] The forming performance of the circuit substrate is evaluated by the resin agglomeration in the circuit substrate, and the number of resin agglomerations N≤10 and the agglomeration size D≤50 um are considered to be up to standard.
[0060] Optionally, the conductive layer is a metal foil layer, such as copper foil.
[0061] The present invention also provides a printed circuit board made of the circuit substrate as described above.
[0062] The printed circuit board is mainly made of the circuit substrate through processes such as drilling, hole filling, micro-etching, pre-preg, activation, acceleration, chemical copper and copper thickening.
[0063] Hereinafter, the resin composition, prepreg, circuit substrate and printed circuit board will be further described through the following specific examples.
[0064] Example 1
[0065] The filler was surface modified: 300 g of spherical silica was weighed and added to 600 mL of deionized water, and the mixture was stirred thoroughly to be evenly dispersed to obtain a silica solution; 1.5 parts by weight of KBM573 and 0.3 parts by weight of KBM5803 were added to 50 mL of anhydrous ethanol, and the mixture was stirred thoroughly for 2 h to be evenly dispersed to obtain a silane coupling agent solution; the silane coupling agent solution was added dropwise to the silica solution, and the mixture was stirred for 6 h to be evenly dispersed, and then filtered and dried to obtain the modified silica.
[0066] A resin composition is prepared by mixing 100 parts by weight of an oligomeric maleimide, whose structural formula is shown in formula (I), wherein R1 is an alkyl group, R2 is an alkyl group, and n is 3, 30 parts by weight of a vinyl-terminated polyisobutylene having a molecular weight of 350 and a terminal olefin content of 10 wt%, 100 parts by weight of modified silica, 55 parts by weight of 1,3-divinyl-2-imidazolidinone, and 0.03 parts by weight of benzoyl peroxide (H 11 =90°C) and 0.01 parts by weight of 2,3-dimethyl-2,3-diphenylbutane (H 13 =220°C), dissolved with butanone and stirred at 25°C at 500 rpm for 20 hours to obtain a resin composition with a solid content of 60%, wherein the curing temperature of the resin composition is 170°C, and the 1-hour half-life temperature of the composite initiator is 160°C.
[0067] The resin composition was impregnated with 1078E glass fiber cloth, and then dried at 150°C to remove the solvent to obtain a prepreg.
[0068] Two of the above-mentioned prepregs were stacked, and both sides were covered with copper foil having a thickness of 12 μm and pressed at a pressure of 30 MPa and 250° C. to prepare a circuit substrate.
[0069] The performance test results of the circuit substrate of this embodiment are shown in Table 1.
[0070] Example 2
[0071] The filler was surface modified: 300 g of spherical silica was weighed and added to 600 mL of deionized water, and the mixture was stirred thoroughly to be evenly dispersed to obtain a silica solution; 1.5 parts by weight of KBM573 and 0.3 parts by weight of KBM5803 were added to 50 mL of anhydrous ethanol, and the mixture was stirred thoroughly for 2 h to be evenly dispersed to obtain a silane coupling agent solution; the silane coupling agent solution was added dropwise to the silica solution, and the mixture was stirred for 6 h to be evenly dispersed, and then filtered and dried to obtain the modified silica.
[0072] A resin composition is prepared by mixing 100 parts by weight of an oligomeric maleimide, whose structural formula is shown in formula (I), wherein R1 is an ether bond, R2 is an alkyl group, and n is 10, 30 parts by weight of a polyisobutylene having an allyl structure and a molecular weight of 500 and a terminal olefin content of 20 wt%, 50 parts by weight of modified silica, 30 parts by weight of 1,3-divinyl-2-imidazolidinone, and 0.03 parts by weight of lauroyl peroxide (H 11 = 80°C), 0.01 parts by weight of dicumyl peroxide (H 12 =140°C) and 0.01 parts by weight of 2,3-dimethyl-2,3-diphenylbutane (H 13 =220°C), dissolved with butanone and stirred at 25°C at 500 rpm for 20 hours to obtain a resin composition with a solid content of 60%, wherein the curing temperature of the resin composition is 170°C, and the 1-hour half-life temperature of the composite initiator is 155°C.
[0073] The resin composition was impregnated with 1078E glass fiber cloth, and then dried at 150°C to remove the solvent to obtain a prepreg.
[0074] Two of the above-mentioned prepregs were stacked, and both sides were covered with copper foil having a thickness of 12 μm and pressed at a pressure of 30 MPa and 250° C. to prepare a circuit substrate.
[0075] The performance test results of the circuit substrate of this embodiment are shown in Table 1.
[0076] Example 3
[0077] The filler was surface modified: 300 g of spherical silica was weighed and added to 600 mL of deionized water, and the mixture was stirred thoroughly to be evenly dispersed to obtain a silica solution; 1.5 parts by weight of KBM573 and 0.3 parts by weight of KBM5803 were added to 50 mL of anhydrous ethanol, and the mixture was stirred thoroughly for 2 h to be evenly dispersed to obtain a silane coupling agent solution; the silane coupling agent solution was added dropwise to the silica solution, and the mixture was stirred for 6 h to be evenly dispersed, and then filtered and dried to obtain the modified silica.
[0078] A resin composition is prepared by mixing 100 parts by weight of an oligomeric maleimide, whose structural formula is shown in formula (I), wherein R1 is an alkyl group, R2 is an alkyl group, and n is 20, 25 parts by weight of a vinyl-terminated polyisobutylene having a molecular weight of 1000 and a terminal olefin content of 30 wt%, 80 parts by weight of modified silica, 40 parts by weight of 1,3,5-triacryloylhexahydro-1,3,5-triazine, and 0.03 parts by weight of 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane (H 12 =152°C) and 0.01 parts by weight of 2,3-dimethyl-2,3-diphenylbutane (H 13 =220°C), dissolved in butanone and stirred at 25°C at 500 rpm for 20 hours to obtain a resin composition with a solid content of 60%, wherein the curing temperature of the resin composition is 170°C, and the 1-hour half-life temperature of the composite initiator is 180°C.
[0079] The resin composition was impregnated with 1078E glass fiber cloth, and then dried at 150°C to remove the solvent to obtain a prepreg.
[0080] Two of the above-mentioned prepregs were stacked, and both sides were covered with copper foil having a thickness of 12 μm and pressed at a pressure of 30 MPa and 250° C. to prepare a circuit substrate.
[0081] The performance test results of the circuit substrate of this embodiment are shown in Table 1.
[0082] Example 4
[0083] The filler was surface modified: 300 g of spherical silica was weighed and added to 600 mL of deionized water, and the mixture was stirred thoroughly to be evenly dispersed to obtain a silica solution; 1.5 parts by weight of KBM974 and 0.3 parts by weight of KBM6803 were added to 50 mL of anhydrous ethanol, and the mixture was stirred thoroughly for 2 h to be evenly dispersed to obtain a silane coupling agent solution; the silane coupling agent solution was added dropwise to the silica solution, and the mixture was stirred for 6 h to be evenly dispersed, and then filtered and dried to obtain the modified silica.
[0084] A resin composition is prepared by mixing 100 parts by weight of an oligomeric maleimide, whose structural formula is shown in formula (I), wherein R1 is an alkyl group, R2 is an alkyl group, and n is 35, 40 parts by weight of a vinyl-terminated polyisobutylene having a molecular weight of 4000 and a terminal olefin content of 50 wt%, 150 parts by weight of modified silica, 60 parts by weight of 1,3,5-triacryloylhexahydro-1,3,5-triazine, and 0.03 parts by weight of benzoyl peroxide (H 11 =90°C), 0.03 parts by weight of dicumyl peroxide (H 12 =140°C) and 0.01 parts by weight of 2,3-dimethyl-2,3-diphenylbutane (H 13 =220°C), dissolved in butanone and stirred at 25°C at 500 rpm for 20 hours to obtain a resin composition with a solid content of 60%, wherein the curing temperature of the resin composition is 170°C, and the 1-hour half-life temperature of the composite initiator is 168°C.
[0085] The resin composition was impregnated with 1078E glass fiber cloth, and then dried at 150° C. for 3 minutes to obtain a semi-cured sheet after removing the solvent.
[0086] Two of the above-mentioned prepregs were stacked, and both sides were covered with copper foil having a thickness of 12 μm and pressed at a pressure of 30 MPa and 250° C. to prepare a circuit substrate.
[0087] The performance test results of the circuit substrate of this embodiment are shown in Table 1.
[0088] Example 5
[0089] The filler was surface modified: 300 g of spherical silica was weighed and added to 600 mL of deionized water, and the mixture was stirred thoroughly to be evenly dispersed to obtain a silica solution; 1 part by weight of KBM573 and 1 part by weight of KBM5803 were added to 50 mL of anhydrous ethanol, and the mixture was stirred thoroughly for 2 h to be evenly dispersed to obtain a silane coupling agent solution; the silane coupling agent solution was added dropwise to the silica solution, and the mixture was stirred for 6 h to be evenly dispersed, and then filtered and dried to obtain the modified silica.
[0090] A resin composition is prepared by mixing 100 parts by weight of an oligomeric maleimide, whose structural formula is shown in formula (I), wherein R1 is an ether bond, R2 is an alkyl group, and n is 45, 5 parts by weight of a vinyl-terminated polyisobutylene having a molecular weight of 2000 and a terminal olefin content of 40 wt%, 150 parts by weight of modified silica, 70 parts by weight of 1,3-divinyl-2-imidazolidinone, 0.01 parts by weight of lauroyl peroxide (H 11 = 80°C), 0.03 parts by weight of tert-butyl cumene peroxide (H 12=144°C) and 0.01 parts by weight of 2,3-dimethyl-2,3-diphenylbutane (H 13 =220°C), dissolved with butanone and stirred at 25°C at 500 rpm for 20 hours to obtain a resin composition with a solid content of 60%, wherein the curing temperature of the resin composition is 170°C, and the 1-hour half-life temperature of the composite initiator is 158°C.
[0091] The resin composition was impregnated with 1078E glass fiber cloth, and then dried at 150°C to remove the solvent to obtain a prepreg.
[0092] Two of the above-mentioned prepregs were stacked, and both sides were covered with copper foil having a thickness of 12 μm and pressed at a pressure of 30 MPa and 250° C. to prepare a circuit substrate.
[0093] The performance test results of the circuit substrate of this embodiment are shown in Table 1.
[0094] Table 1
[0095]
[0096] Example 6
[0097] The difference between Example 6 and Example 4 is that the first resin is a biphenyl epoxy resin, wherein the curing temperature of the resin composition is 170°C, and the one-hour half-life temperature of the composite initiator is 168°C.
[0098] The performance test results of the circuit substrate of this embodiment are shown in Table 2.
[0099] Example 7
[0100] The difference between Example 7 and Example 4 is that the first resin is bismaleimide (BMI-70), wherein the curing temperature of the resin composition is 170° C., and the one-hour half-life temperature of the composite initiator is 168° C.
[0101] The performance test results of the circuit substrate of this embodiment are shown in Table 2.
[0102] Table 2
[0103]
[0104] Example 8
[0105] The difference between Example 8 and Example 4 is that the terminal olefin content of the second resin is 70 wt %, wherein the curing temperature of the resin composition is 170° C., and the one-hour half-life temperature of the composite initiator is 168° C.
[0106] The performance test results of the circuit substrate of this comparative example are shown in Table 3.
[0107] Example 9
[0108] The difference between Example 9 and Example 4 is that the polyisobutylene resin does not contain terminal olefin groups, wherein the curing temperature of the resin composition is 170° C., and the one-hour half-life temperature of the composite initiator is 168° C.
[0109] The performance test results of the circuit substrate of this comparative example are shown in Table 3.
[0110] Table 3
[0111]
[0112]
[0113] Example 10
[0114] The difference between Example 10 and Example 4 is that only KBM573 is used to modify the silica to obtain the modified silica, wherein the curing temperature of the resin composition is 170° C., and the 1-hour half-life temperature of the composite initiator is 168° C.
[0115] The performance test results of the circuit substrate of this embodiment are shown in Table 4.
[0116] Embodiment 11
[0117] The difference between Example 11 and Example 4 is that only KBM5803 is used to modify the silica to obtain the modified silica, wherein the curing temperature of the resin composition is 170° C., and the 1-hour half-life temperature of the composite initiator is 168° C.
[0118] The performance test results of the circuit substrate of this embodiment are shown in Table 4.
[0119] Table 4
[0120]
[0121] Example 12
[0122] The difference between Example 12 and Example 4 is that the initiator uses 0.05 parts by weight of benzoyl peroxide (H 11 =90°C) and 0.01 parts by weight of 2,3-dimethyl-2,3-diphenylbutane (H 13 =220°C), wherein the curing temperature of the resin composition is 170°C and the 1-hour half-life temperature of the composite initiator is 160°C.
[0123] The performance test results of the circuit substrate of this embodiment are shown in Table 5.
[0124] Embodiment 13
[0125] The difference between Example 13 and Example 4 is that the initiator uses 0.05 parts by weight of diisopropylbenzene peroxide (H 12 =140°C) and 0.01 parts by weight of 2,3-dimethyl-2,3-diphenylbutane (H 13 =220°C), wherein the curing temperature of the resin composition is 170°C and the 1-hour half-life temperature of the composite initiator is 187°C.
[0126] The performance test results of the circuit substrate of this embodiment are shown in Table 5.
[0127] Embodiment 14
[0128] The difference between Example 14 and Example 4 is that the initiator uses 0.05 parts by weight of cumene hydroperoxide (H 12 =190°C), wherein the curing temperature of the resin composition is 170°C and the 1-hour half-life temperature of the composite initiator is 190°C.
[0129] The performance test results of the circuit substrate of this embodiment are shown in Table 5.
[0130] Table 5
[0131]
[0132] Embodiment 15
[0133] The difference between Example 15 and Example 4 is that trivinylbenzene is used as the curing agent, wherein the curing temperature of the resin composition is 170°C, and the one-hour half-life temperature of the composite initiator is 168°C.
[0134] The performance test results of the circuit substrate of this embodiment are shown in Table 6.
[0135] Table 6
[0136]
[0137] Comparative Example 1
[0138] The difference between Comparative Example 1 and Example 4 is that the initiator is 0.03 parts by weight of 2,3-dimethyl-2,3-diphenylbutane (H 13 =220°C), wherein the curing temperature of the resin composition is 170°C and the one-hour half-life temperature of the initiator is 220°C.
[0139] The performance test results of the circuit substrate of this comparative example are shown in Table 7.
[0140] Comparative Example 2
[0141] The difference between Comparative Example 2 and Example 4 is that the initiator is 0.03 parts by weight of diisopropylbenzene peroxide (H 12 =140°C), wherein the curing temperature of the resin composition is 170°C and the one-hour half-life temperature of the initiator is 140°C.
[0142] The performance test results of the circuit substrate of this comparative example are shown in Table 7.
[0143] Table 7
[0144]
[0145] Comparative Example 3
[0146] The difference between Comparative Example 3 and Example 4 is that the first resin is selected from 1,1'-(2,2,4-trimethyl-1,6-hexanediyl)bis-1H-pyrrole-2,5-dione resin having no cyclic conjugated structure in the molecular chain, wherein the curing temperature of the resin composition is 170°C and the 1-hour half-life temperature of the composite initiator is 168°C.
[0147] The performance test results of the circuit substrate of this comparative example are shown in Table 8.
[0148] Comparative Example 4
[0149] The difference between Comparative Example 4 and Example 4 is that the second resin is selected from hydrogenated polyisobutylene resin without saturated double bonds, wherein the curing temperature of the resin composition is 170° C., and the one-hour half-life temperature of the composite initiator is 168° C.
[0150] The performance test results of the circuit substrate of this comparative example are shown in Table 8.
[0151] Comparative Example 5
[0152] The difference between Comparative Example 5 and Example 4 is that the second resin is selected from a polybutadiene resin having an alkyl group with a branched carbon chain length of 3 and a branch density of 25 branches per 10,000 main chain carbon atoms, wherein the curing temperature of the resin composition is 170°C and the 1-hour half-life temperature of the composite initiator is 168°C.
[0153] The performance test results of the circuit substrate of this comparative example are shown in Table 8.
[0154] Table 8
[0155]
[0156] The performance tests of the above embodiments and comparative examples are as follows:
[0157] XY-axis thermal expansion coefficient: A circuit substrate with a width of 4 mm and a length of 25 mm was taken as the test sample. A thermal mechanical analyzer from TA was used. A tensile measurement fixture was used with a distance of 15 mm between the clamps. A load of 50 mN was applied. The temperature was raised from room temperature to 260°C at a rate of 10°C / min. The expansion in the XY-axis direction was measured. The average linear expansion rate of the expansion curve from 50°C to 130°C was taken as CTE.
[0158] Bending modulus: A circuit substrate with a length of 76.2 mm and a width of 25.4 mm is taken as a test sample and measured using a material testing machine with a span of 25.4 mm and a test speed of 0.76 mm / min to obtain the bending modulus.
[0159] Impact crack: Place the circuit board on a glass slide, use a micro Vickers hardness tester (HMV-G, manufactured by Shimadzu Corporation) to load 2kgf for 15 seconds, and apply loads to 10 locations of the circuit board. For each of the 10 locations, confirm whether there are cross-shaped cracks or cracks. If there are cracks, measure the longitudinal and transverse lengths of the cracks respectively; if no cracks are observed, the length of the crack is set to 0. Based on the longitudinal and transverse lengths of the 10 locations, calculate the average value of the crack length, and set the average value X≤200μm or less as "AA", the average value 200μm<X≤1000μm as "BB", and the rest as "CC".
[0160] Resin agglomeration: Cut a circuit substrate with a length of 1 cm as a test sample, fill it with glue and make slices, observe the resin agglomeration of the cross-section of the slice sample through a scanning electron microscope (SEM), and then count the size and number of resin agglomeration points, and set the situation where there is no agglomeration as "A"; the situation where the number N≤10 and the agglomeration size D≤10um is set as "B"; the situation where the number N≤10 and the agglomeration size 10um<D≤50um is set as "C"; the situation where the number N>10 and the agglomeration size is arbitrary is set as "D".
[0161] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0162] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A resin composition, characterized in that The resin composition comprises a first resin, a second resin, a curing agent, a filler and an initiator, wherein the first resin has a cyclic conjugated structure in its molecular chain, the second resin is selected from a linear resin containing unsaturated double bonds and no branches, the one-hour half-life temperature of the initiator is H1, the curing temperature of the resin composition is H2, and H2-20≤H1≤H2+20.
2. The resin composition according to claim 1, characterized in that The curing temperature of the resin composition is 130°C to 250°C.
3. The resin composition according to claim 1, characterized in that The initiator is selected from peroxide initiators and / or carbon-based initiators.
4. The resin composition according to claim 3, characterized in that The initiator is selected from the peroxide initiator and the carbon-based initiator, wherein the peroxide initiator is selected from the first initiator and / or the second initiator, and the one-hour half-life temperature of the first initiator is H 11 , 50℃≤H 11 <120°C, the one-hour half-life temperature of the second initiator is H 12 , 120℃≤H 12 ≤190°C, the one-hour half-life temperature of the carbon-based initiator is H 13 , H 13 ≥190℃.
5. The resin composition according to claim 4, characterized in that The first initiator is selected from at least one of benzoyl peroxide, lauroyl peroxide or t-butyl peroxyvalerate; And / or, the second initiator is selected from at least one of di-tert-butyl peroxycyclohexane, di-tert-butyl peroxyethyl butyrate, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, diisopropylbenzene peroxide, tert-butyl isopropylbenzene peroxide, tert-amyl hydroperoxide, isopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-dichloroperoxyhexane, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide or 1,1,3,3-tetramethyl hydroperoxide; And / or, the carbon-based initiator is at least one selected from 2,3-dimethyl-2,3-diphenylbutane or p-isopropylbenzene polymer.
6. The resin composition according to claim 1, characterized in that The number average molecular weight of the second resin is 300 to 5000; And / or, the second resin further includes terminal olefin groups, and the content of the terminal olefin groups in the second resin is 10 wt % to 60 wt %.
7. The resin composition according to claim 1, characterized in that The first resin is selected from at least one of maleimide resin, epoxy resin, benzoxazine resin, polyphenylene ether resin or polyimide resin.
8. The resin composition according to claim 7, characterized in that The molecular structure of the maleimide resin is formula (I): Wherein, n=3-48, R1 is an alkyl group or an ether bond, and R2 is an alkyl group.
9. The resin composition according to any one of claims 1 to 8, characterized in that In the resin composition, based on 100 parts by weight of the first resin, the amount of the second resin is 5 parts by weight to 50 parts by weight, the amount of the curing agent is 30 parts by weight to 70 parts by weight, the amount of the filler is 50 parts by weight to 200 parts by weight, and the amount of the initiator is 0.005 parts by weight to 0.1 parts by weight.
10. The resin composition according to claim 1, characterized in that The filler is selected from inorganic fillers, and the filler is modified by a silane coupling agent.
11. The resin composition according to claim 10, characterized in that The silane coupling agent is selected from a first silane coupling agent and a second silane coupling agent, wherein the first silane coupling agent contains an alkenyl radical and has a carbon chain length of ≤6, the carbon chain length of the second silane coupling agent is >6, and / or the mass ratio of the first silane coupling agent to the second silane coupling agent is 1:0.05 to 1:1.
5.
12. A prepreg made from the resin composition according to any one of claims 1 to 11.
13. A circuit substrate made of the prepreg as claimed in claim 12.
14. A printed circuit board made of the circuit substrate as claimed in claim 13.